Pendekatan Analisis Kualitatif Manajemen Pengetahuan - Artono; Oktaria Ardika Putri; Annisa Aulia Azizah (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2022)
Of course, in an era like today, knowledge management is a crucial thing, where the development of knowledge management is currently very fast. Several proposals for the classification of the main approaches to knowledge management are considered and their relationships and differences are discussed. Three main groups emerge: measuring knowledge, managing knowledge (either with a greater emphasis on human factors or on information technology), and creating knowledge. The main contribution of this study is the compilation of literature on knowledge management and creation, together with an analysis of the researchers' own proposals for the classification of different approaches, depending on their more descriptive or more normative perspective.